Effect of electron–positron plasma production on the generation of a magnetic field in laser-plasma interactions. (October 2021) - Samsonov, A S; Nerush, E N; Kostyukov, I Yu
Abstract: We consider the effect of electron–positron pair production on the generation of a quasi-stationary magnetic field in the interaction of an ultra-intense circularly polarised laser pulse with a thick plasma target. Full-scale three-dimensional numerical simulations by the particle-in-cell method performed taking into account quantum electrodynamic effects indicates a qualitative change in the generation of the magnetic field at a laser radiation intensity Ɩ ≳ 10 24 W cm -2, which gives rise to a macroscopic number of electron–positron pairs. In this case, the amplitude of the magnetic field increases with an increase in the radiation intensity, whereas the amplitude of the magnetic field is hardly intensity-dependent when the effect of electron–positron pair production is neglected.